HARMONI DALAM PERBEDAAN, (PENDIDIKAN MULTIKULTURAL SEBAGAI PILAR UTAMA DALAM MEMPERERAT PERSATUAN BANGSA) - Meyniar Albina (Cemara Education and Science, 2024)
Abstract Differences in language, customs and culture in Indonesian society are a reality that cannot be denied. This is indeed recognized by the Indonesian people, and will continue to happen in the past, present and in the future. The diversity of Indonesian society can be a blessing because it brings extraordinary cultural riches. This cultural wealth, if processed wisely, will become a beautiful mosaic and national strength. National strength is not only needed to strengthen national unity and unity but also to provide equality, equity and justice for every person, community and culture in Indonesia to realize prosperity. actively participate in state and nation development. In this journal, we will discuss efforts to unite the culture of multiculturalism which aims to provide understanding and experience of the Indonesian people and nation regarding multiculturalism. the meaning of the spirit of togetherness, mutual respect, mutual love, mutual tolerance and mutual understanding of each other, despite different races, ethnicities, cultures, religions and beliefs. The data obtained in this article uses the library research method.